Students’ Attitudes and Perceptions Towards Plastics and Microplastics Pollution: Implications for Vietnam - Dang, Mai Hai (VNU Journal of Science: Legal Studies, 2025)
Economic growth, urbanization, and population expansion have contributed to the increase in plastic waste, intensifying Vietnam's plastic pollution in recent years. Human behavior plays a crucial role both in the creation and reduction of plastic pollution. This study applies the Theory of Planned Behavior to examine students' perceptions and attitudes toward plastic and microplastic pollution. The results indicate that attitude is the strongest predictor of behavioral intention (β = 0.411, p < 0.001). Perceived behavioral control also influences behavioral intention, though to a lesser extent (β = 0.162, p < 0.001). These findings suggest that raising awareness and changing students’ attitudes through education and communication play an important role in promoting behavior that reduces plastic consumption.